Impact of childhood asthma on growth trajectories in early adolescence: Findings from the Childhood Asthma Prevention Study (CAPS). Issue 3 (8th November 2016) - Movin, Maria; Garden, Frances L.; Protudjer, Jennifer L.P.; Ullemar, Vilhelmina; Svensdotter, Frida; Andersson, David; Kruse, Andreas; Cowell, Chris T.; Toelle, Brett G.; Marks, Guy B.; Almqvist, Catarina; ,
ABSTRACT: Background and objective: Understanding the associations between childhood asthma and growth in early adolescence by accounting for the heterogeneity of growth during puberty has been largely unexplored. The objective was to identify sex‐specific classes of growth trajectories during early adolescence, using a method which takes the heterogeneity of growth into account and to evaluate the association between childhood asthma and different classes of growth trajectories in adolescence. Methods: Our longitudinal study included participants with a family history of asthma born during 1997–1999 in Sydney, Australia. Hence, all participants were at high risk for asthma. Asthma status was ascertained at 8 years of age using data from questionnaires and lung function tests. Growth trajectories between 11 and 14 years of age were classified using a latent basis growth mixture model. Multinomial regression analyses were used to evaluate the association between asthma and the categorized classes of growth trajectories. Results: In total, 316 participants (51.6% boys), representing 51.3% of the entire cohort, were included. Sex‐specific classes of growth trajectories were defined. Among boys, asthma was not associated with the classes of growth trajectories. Girls with asthma were more likely than girls without asthma to belong to a class with later growth (OR: 3.79, 95% CI: 1.33, 10.84). Excluding participants using inhaled corticosteroids or adjusting for confounders did not significantly change the results for either sex. Conclusion: We identified sex‐specific heterogeneous classes of growth using growth mixture modelling. Associations between childhood asthma and different classes of growth trajectories were found for girls only. Abstract : The association between childhood asthma and heterogeneous sex‐specific classes of growth trajectories during adolescence was investigated. No differences were found for boys with versus without asthma. However, girls with asthma had a higher probability of belonging to a class with later growth than those without asthma.